Kim Jong Il's death : end of an era? - Euan, Graham (2012)
Kim Jong Il’s demise has a broader resonance, rounding off an annus horribilis for dystopian despots worldwide. Even with an orderly transfer of power to his son, Kim Jong Un, the ‘Dear Leader’s’ brand of leadership will be hard to replicate under North Korea’s straitened circumstances.